1976
DOI: 10.1002/1097-0142(197609)38:3<1199::aid-cncr2820380321>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pulmonary leiomyomatous hamartomas.Report of a case with ultrastructure examination

Abstract: The electron microscopic features of pulmonary leiom yomatous hamartoma, a very rare neoplasm, were studied. Characteristic smooth muscle cells containing microfilaments, dense bodies, plaques, pinocytotic vesicles, and basal lamina were present. Fibrosis was minimal, which supports the belief that this component is a secondary phenomena.Cancer 38:1199-1204, 1976. ULTIPLE PULMONARY FIBROLEIOMYOMATOUSM hamartomas are extremely rare benign lung lesions seen in asymptomatic middle-aged female patients. Apparently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 6 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…Multiple pulmonary leiomyomatous hamartoma (MPLH) is a rare lesion seen mainly in middle‐aged women 1 . The individual lesions are composed of an admixture of mature tissue, including smooth muscle, collagenous fibrous tissue and glandular elements.…”
mentioning
confidence: 99%
“…Multiple pulmonary leiomyomatous hamartoma (MPLH) is a rare lesion seen mainly in middle‐aged women 1 . The individual lesions are composed of an admixture of mature tissue, including smooth muscle, collagenous fibrous tissue and glandular elements.…”
mentioning
confidence: 99%
“…In earlier reports, the term leiomyomatous hamartoma has been used for these tumors when they appear to be multicentric. [14][15][16][17] Some researchers, however, have suggested that such neoplasms should not be considered to be primary lesions of the lung but should rather be regarded as metastatic tumors.…”
Section: Leiomyomamentioning
confidence: 99%
“…In 1999 we reported on a 31‐year‐old woman with multiple pulmonary leiomyomatous hamartoma (MPLH) 1 . MPLH is a peculiar lesion of the lung, the individual lesions of which are composed of a mixture of smooth muscle and glandular elements 2 . There is no apparent topographical relationship between the lesion and the bronchial trees or vascular structures, although a previous ultrastructural study suggests a possible relation to the contractile system of the lung acini 3 .…”
mentioning
confidence: 99%
“…There is no apparent topographical relationship between the lesion and the bronchial trees or vascular structures, although a previous ultrastructural study suggests a possible relation to the contractile system of the lung acini 3 . MPLH is not associated with specific pathological conditions of the lung, including interstitial pneumonia or lymphangioleiomyomatosis, whereas there has been controversy regarding whether MPLH is equivalent to benign metastasizing leiomyoma 2,4–8 . The clinical course of MPLH also remains unclear, because there have been a few reports of long‐term follow up of patients with MPLH 9,10…”
mentioning
confidence: 99%
See 1 more Smart Citation